The Effect of L-Arginine Supplementation in Feed on Body Weight and Carcass Percentage of Broiler Chickens - Uduk, Mersiana; Lisnahan, Charles V; Purwantiningsih, Theresia I. (Journal of Tropical Animal Science and Technology, 2025)
This study aimed to determine the effect of  L-arginine supplementation in feed on live weight and carcass percentage of  broiler chickens. This research has been carried out in the Animal Husbandry Study Program and Laboratory of the Faculty of Agriculture, University of Timor for 42 days, from March to May 2022. This study used 96 broiler chickens aged 14 days. The method used in this study was a completely randomized design consisting of 4 treatments and 4 replications. The treatments were T0 (control feed), T1 (L-arginine supplementation 0.50%), T2 (L-arginine supplementation 0.75%) and T3 (L-arginine supplementation 1.00%). The variables observed in this study were live weight, carcass weight, breast weight, thigh weight and breast thickness of broiler chickens. The data obtained were analyzed using Analysis of Variance Prints and Duncan's Test. Statistical analysis showed that the treatment had a significant effect on live weight, carcass weight, chest weight, thigh weight and chest thickness (P<0.05). It can be concluded that supplementation of L-arginine 0.75% in feed increased live weight and carcass percentage of broiler chickens. Keywords: Broiler Chicken, L-arginine, Live Weight, percentage carcass